The Effectiveness of the Cooperative Learning Model in Improving Reading Comprehension Ability in Fifth-Grade Students - Husyainah, Hasibuan; Rahmat Kartolo; Sutikno (International Journal of Educational Research Excellence, 2026)
This research is motivated by initial observations at SD Negeri 153 Kayulaut, Mandailing Natal Regency, indicating low reading comprehension abilities among fifth-grade students in the 2025-2026 academic year. This study aimed to test the effectiveness of the Cooperative Learning model in improving the reading comprehension ability of fifth-grade students at SD Negeri 153 Kayulaut. A quantitative approach with a quasi-experimental design was used in this research, involving 42 fifth-grade students divided into two groups: an experimental group (21 students) who received treatment with the Cooperative Learning model, and a control group (21 students) who continued with conventional learning. Data collection techniques included tests (pre-test and post-test), observation, and documentation. Data were analyzed using normality tests, homogeneity tests, and t-tests to determine the significance of differences between groups. In Cycle I, the average reading comprehension score for the experimental class was 59.62 with a classical completeness of 42.86%. This figure increased sharply in Cycle II to 69.14 with a completeness of 61.90%, and reached 77.19 with a classical completeness of 90.48% in Cycle III. This increase far surpassed the control class, which only showed an average of 53.24 (33.33% completeness) in Cycle I, 61.43 (47.62% completeness) in Cycle II, and actually decreased to 56.76 (14.29% completeness) in Cycle III, after a temporary increase. In addition to the improvement in learning outcomes, observations of experimental class student activity also showed consistent improvement, from an average of 58.75% in Cycle I to 72.5% in Cycle II, and reaching 85% in Cycle III. The research results indicate that the application of the Cooperative Learning model significantly improves the reading comprehension ability of fifth-grade students at SD Negeri 153 Kayulaut, Mandailing Natal Regency, Academic Year 2025-2026